PENGUJIAN TEG SP1848 SEBAGAI PEMBANGKIT LISTRIK DENGAN SISI PANAS MENGGUNAKAN SETRIKA BERTEMPERATUR 75°C - catur arief wijaksono; Fildzah Raazzaq; Zanu Saputra; Ocsirendi Ocsirendi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Thermoelectric Generator (TEG) is a technology that can convert heat energy into electrical energy directly due to the difference in temperature between the hot side and cold side of the thermoelectric module, known as the Seebeck effect. This study uses a thermoelectric module of the SP 1848 type. An aluminum plate is used as a medium for absorbing heat from a simulated iron temperature with a maximum temperature of 75°C, while the cold side of the thermoelectric module uses a heatsink with a temperature of 33°C and a fan. From the tests carried out, the maximum voltage produced when two TEG modules are connected in series is 1.65 Volt with a temperature difference of 43.13°C. The maximum current generated when two TEG modules are connected in parallel is 3.52 Ampere with a temperature difference of 42°C.